Killing machines : Trump, the law of war, and the future of military impunity / Thomas Gift, University College London. - Gift, Thomas (Cambridge University Press, 2026)
What causes a Western democratic leader to stop even feigning to value the law of war? Unlike past US presidents, who at least paid lip service to the law of armed conflict, Donald Trump has openly flouted it: pardoning war criminals; denigrating the Geneva Conventions; praising torture; and discarding military norms of restraint. This gripping account depicts how Trump has upended assumptions about America's outward commitment to the law of war, exposing the conditions that make such defiance possible. Drawing on in-depth case studies and original survey analysis, Thomas Gift explains how Trump has relied on right-wing media and allies in Congress to attack the law of war - not in the shadows, but in broad daylight. Killing Machines cautions that Trump's approach is not an aberration - it's a playbook other leaders could follow. This title is also available as Open Access on Cambridge Core.